1996
DOI: 10.1183/09031936.96.09071389
|View full text |Cite
|
Sign up to set email alerts
|

Lungs in thalassaemia major patients receiving regular transfusion

Abstract: Progressive tissue iron deposition from multiple blood transfusions is common in beta-thalassaemia and pulmonary iron deposition may result in parenchymal damage. The objectives of this study were to: 1) determine the predominant pulmonary dysfunction in patients with thalassaemia major; and 2) demonstrate that parenchymal disease, if present, is at the level of the alveolocapillary membrane.Fourteen thalassaemia major patients (13 nonsmokers) receiving regular blood transfusion and without any history of chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
60
3
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 33 publications
9
60
3
7
Order By: Relevance
“…We found that patients with TM have decreased aerobic capacity (decreased V O2 max), in agreement with the literature [4][5][6][7][8][9][10][11][12][13]. Only one article did not find decreased exercise capacity in TM patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that patients with TM have decreased aerobic capacity (decreased V O2 max), in agreement with the literature [4][5][6][7][8][9][10][11][12][13]. Only one article did not find decreased exercise capacity in TM patients.…”
Section: Discussionsupporting
confidence: 91%
“…Exercise capacity is reduced in patients with TM [4][5][6][7][8][9][10][11][12][13] and most studies have attributed these findings to a combination of anemia and iron-mediated cardiotoxicity [4,6,7,10]. Cardiopulmonary exercise function testing has been proposed as a noninvasive test to detect early cardiac dysfunction [7]; however, the ability to detect cardiac iron with exercise testing is largely unvalidated.…”
Section: Introductionmentioning
confidence: 99%
“…Among the thalassemic subjects, restrictive lung function abnormality was the most common (42/63) observation documented in this study. Our findings are consistent with those of Carnelli et al, 1 Factor et al, 2 Tai et al, 5 Luyt et al, 6 and Filosa et al 7 What is unique to our study is that it was performed exclusively in children, while those studies mentioned earlier were all performed in both children and adults, with a considerably older mean age. Therefore, our study shows that lung dysfunction in thalassemic patients has occurred since childhood.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies find a significant inverse correlation between total lung capacity and iron burden 1-3 as well as between total lung capacity and age. 1,2 Others find that neither age 4 nor iron load 4,5,8 correlated with pulmonary function. To our knowledge, no data on this issue is available in Indonesia.…”
mentioning
confidence: 99%
See 1 more Smart Citation